Mattering and life satisfaction among the quarantined adults in Malaysia during the COVID-19 pandemic - Kususanto Ditto Prihadi; Edward S.Z. Lim; EeVonne Sim; Kam Yan Chong (Intelektual Pustaka Media Utama, 2021)
This study aims to investigate the role of mattering, trait extraversion and perceived social inclusion in developing the sense of life satisfaction among adults who reside in Malaysia during the quarantine period amidst the Pandemic in March-June 2020. Previous studies indicated that mattering was a robust predictor of life satisfaction; however, the nature of the quarantine might have affected the perception of social inclusion among individuals with certain levels of extraversions. Therefore, we hypothesized a moderated mediation model; mattering will interact with trait extraversion in predicting life satisfaction, and the prediction is mediated by perceived inclusion. Three hundred and ninety participants were voluntarily recruited to respond to scales such as Life Satisfaction Inventory, State Self-Esteem Scale, General Mattering Scale and the extraversion facet in Big Five Inventory. The scales, demography questions, and informed consent were accessible by online link given to the participants through social media. The analysis was conducted by using PROCESS Macro model eight for statistical product and service solutions (SPSS) applying the Bootstrap analysis with 5000 samples and 95% confidence interval. The result suggested that the hypothesis was confirmed; perceived inclusion levels significantly mediated the association between mattering and life satisfaction among individuals with low and moderate levels of extraversion. However, full mediation only applied among the individuals with moderate extraversion, because among those with low extraversion, mattering was still a significant predictor of life satisfaction.